NEOLIBERAL URBAN POLICIES AND ARCHISTAR SYSTEM: LANDSCAPE REGENERATION OR PRODUCTION OF ALIEN SCENARIOS? - Luca Ruggiero (European Regional Science Association (ERSA), 2010)
The work is the product of a critical reflection on the results of some of the most recent processes that affect the city and contribute to built the enigmatic and complex landscape of the twenty-first century city. The paper focuses, in particular, on the role that culture, architecture, innovation, creativity and tourism play in neo-liberal urban policies. These are often run by 'visionary leaderships' which invest heavily in initiatives, plans and projects which have the intent of conferring a sense of space and place to public areas and build vital and attractive cities and neighbourhoods. The central part of the work is dedicated to the analysis of the transformations in urban landscape conducted by architects and town planners and to the highly debated processes they activate with regard to residents and visitors. The differences in these processes of urban transformation are often significant, especially with regard to their value, social impact, force of attraction, creative, artistic and technological capacity and ability to shape the future of the city and its lifestyles. Not less discussed are the options for the creation, modification and use of urban space, its sustainability and quality of life.
Keywords: 330